2011
DOI: 10.1111/j.1741-3729.2011.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Poverty and Maternal Fears of Children's Outdoor Play

Abstract: Investigating children’s outdoor play unites scholarship on neighborhoods, parental perceptions of safety, and children’s health. Utilizing the Fragile Families and Child Well-being Study (N=3,448), we examine mothers’ fear of their five-year-old children playing outdoors, testing associations with neighborhood social characteristics, city-level crime rates, maternal mental health, and social support. Living in public housing, perceptions of low neighborhood collective efficacy, and living in a Census tract wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 73 publications
3
39
0
2
Order By: Relevance
“…As a result, they may hold greater fears for their children's safety, or genuinely perceive them to be at greater risk. For instance, Kimbro and Schachter (2011) found higher levels of maternal fear among those living in more deprived neighbourhoods (Kimbro & Schachter, 2011). Second, deprived neighbourhoods are often characterised by more physical disorder (e.g., litter, graffiti, vandalism) (Caughy, O'Campo, & Patterson, 2001;Foster, Giles-Corti, & Knuiman, 2011;Hill, Ross, & Angel, 2005;King, 2008;Lee, Booth, Reese- Regan, & Howard, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…As a result, they may hold greater fears for their children's safety, or genuinely perceive them to be at greater risk. For instance, Kimbro and Schachter (2011) found higher levels of maternal fear among those living in more deprived neighbourhoods (Kimbro & Schachter, 2011). Second, deprived neighbourhoods are often characterised by more physical disorder (e.g., litter, graffiti, vandalism) (Caughy, O'Campo, & Patterson, 2001;Foster, Giles-Corti, & Knuiman, 2011;Hill, Ross, & Angel, 2005;King, 2008;Lee, Booth, Reese- Regan, & Howard, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Scholars have undertaken important ethnographies and other qualitative (and quantitative) projects studying the daily lives of low-income and poor residents. From attitudes about marriage (Edin 2000) to perceptions of and worries about violence and crime (Duck 2009;Kimbro and Schachter 2011) to views about neighborhood advantage and social support (Turney and Harknett 2010), researchers have examined a range of issues, asking questions of those most impacted by them.…”
Section: Micro Contextmentioning
confidence: 99%
“…Crime infects all aspects of residents' lives, whether they are 'decent' or 'street' (Anderson 1999;Duck 2009Duck , 2012, especially as a stressor for parents raising children (Dahl, Ceballo, and Huerta 2010;Kimbro and Schachter 2011). Although violent crime has decreased over the last few decades across the USA (Levitt 2004;Blumstein and Wallman 2005), research indicates that crime rates vary with neighborhood context and, importantly, are worse in low-income and poor neighborhoods, although there are exceptions (see, e.g., Cancino, Martinez, and Stowell 2009;Sampson, Raudenbush, and Earls 1997;Thompson and Gartner 2014).…”
Section: Micro Contextmentioning
confidence: 99%
“…A study conducted by Kimbro and Schachter (2011) on 3,448 mothers and children living in cities in the United States found that mothers who lived in poverty-stricken areas feared for their children's safety during outdoor play, which may have restricted the child's free playtime. Another study conducted by Bartie et al (2016) in a low socioeconomic community in South Africa found that some parents felt the environment was safe for their children, but most parents were concerned about their children's safety and stated that they would rather their children play indoors to prevent them from getting abducted.…”
Section: Sub-theme 32: Children's Safety and Lack Of Resourcesmentioning
confidence: 99%